Conceptualizing Food Literacy: A Literature Review - Pamela Farrell (Canadian Society for Studies in Education, 2021)
Food literacy is a complex and multifaceted concept but generally encompasses the knowledge, skills, behaviour and attitudes related to food. Over the last decade, the definition of food literacy has been expanded beyond food skills and nutrition knowledge to include food environments and the food system, but also contextual influences such as sociocultural and socio-economic factors. More recently scholars argue for a critical view of food literacy that takes into account the power imbalances of our food system prompting us to consider questions related to healthy food access, increased corporate food system control, who profits, and who loses (Renwick & Powell, 2019; Sumner, 2015). As schools, community organizations, and policy makers continue to turn to food literacy to promote healthier dietary behaviours and increase population health, this review seeks to conceptualize the broadened understanding of food literacy and shed light on the critical and contextual aspects of food literacy.